PERANAN PUPUK ORGANIK CAIR TERHADAP KUALITAS HIJAUAN PAKAN TERNAK (HPT) ASAL TANAMAN PADI RATOON - Munir, Jamilah; Mulyani, Sri; Yusnaweti, Yusnaweti (JURNAL AGRONIDA, 2019)
The research had been done in Nagari Ikur Lubuk Padang Panjang East District, Padang Panjang City, with a height of 720 m above sea level. The experiments were conducted on March 2017-July 2017. The aimed of this research was to obtain the best variety of rice and liquid organic fertilizer to produce a good forage feed. The experiments were arranged in a split-plot, the main plot being the rice crop; Cisokan and Pandan Wangi. The subplot consists of three types of organic liquid fertilizer (OLF), namely; Crocober Plus, Unitas Super, and NASA Commercial LOF replicate 3 times to 18 plots. Forage pruning was done at 30 days after cutting ratoon. The data obtained were analyzed by F test 5% real level, if the treatment had real effect followed by Significant Difference (LSD) test 5% real level. The included proximate analysis, digestibility of crude protein, fat, crude fiber, organic matter, dry matter, acid detergent fiber (ADF), neutral detergent fiber (NDF), hemicellulose, cellulose, and an extract substance without nitrogen. The results can be concluded that the Pandan Wangi rice is able to produce the highest fresh weight of forage feed if given by 10% OLF of a Unitas Super. Keywords: Cisokan, forage animal feed, organic liquid fertilizer, Pandan Wangi, ratoon rice crop